Role of the cell wall in freezing tolerance of plants - Weiser, Russell L., author; Wallner, Stephen J., advisor; Ross, Cleon, committee member; Stanwood, Phillip, committee member; Towill, Leigh E., committee member (Colorado State University. Libraries, 1989)
Acoustic emissions were observed during freezing of woody supercooling (Fraxinus americana, Malus x 'Dolgo', Pyrus communis, and Fraxinus pennsylvanica) and nonsupercooling species (Pinus edulis, Pinus ponderosa, and Cornus sericea). Observations of hundreds of samples revealed several consistent responses. Acoustic emissions were in no case associated with the high temperature exotherm (extracellular freezing) and are therefore not a result of ice formation per se. The emissions just preceded the low temperature exotherm in supercooling species and stopped at the same time intracellular freezing was completed (near -40°C). Although some acoustic emissions occurred during freezing of non-supercooling species the quantity was considerably less. The concept of negative turgor as a cause of cavitation of cellular water, detected as acoustic emissions, is proposed to explain these observations. When etiolated pea (Pisum sativum) cv. Alaska) seedlings were acclimated at 2°C, changes in several cell wall properties were observed. The weight of the cell wall increased by 40% and arabinosyl content doubled while other glycosyl residues and cellulose remained essentially unchanged. The level of hydroxyproline increased by 80%. Arabinose and especially hydroxyproline are indicators of the glycoprotein extensin. The increase in these components translates to a significant increase in this cell wall structural protein. Measurement of the mRNA for extensin by Northern blot analysis revealed a more than 3-fold increase in the total of all transcripts found (6.0, 4.5, 3.5, 2.6, 2.3, and 1.5 kilobases), while increases in certain transcripts (6.0, 2.6, and 1.5 kilobases) appeared to be especially promoted. The possible structural role of extensin in freezing tolerance and its regulation at the gene level are examined. Pea epicotyls grown in osmotic stress up to -1.15 MPa imposed by growth in polyethylene glycol solutions were visibly stunted and became 10°C more tolerant to freezing. During this period extensin level in the cell wall increased significantly. When water was withheld from etiolated seedlings the water potential dropped from -0.42 to -1.14 MPa and was coincident with a 7°C increase in freezing tolerance, a 44% increase in cell wall extensin, and a dramatic drop in extensin mRNA. In both water stress treatments there was no specific increase in extensin mRNA transcripts identified at 6.0, 4.5, 3.5, 2.6, 2.3, 1.8, and 1.5 kilobases. Pea epicotyls that were either wounded or exposed to ethylene showed no clear change in freezing tolerance, or total extensin mRNA, but had a significant rise in cell wall extensin. The same mRNA transcripts were found with the addition of a band at 1.2 kilobases. Interestingly, the 1.5 kilobase transcript was upregulated significantly more than other bands in both wounded and ethylene treated peas.
Covers not scanned.
Keywords: Plant cell walls; Plants -- Effect of cold on; Plants -- Frost resistance